Original articleRisk factors of postpartum depression in Ramhormoz city, Iran - Cheraghi, Maria; Najafian, Mahin; Amoori, Neda; Bazargan, Asma; Cheraghi, Marjan; Motaghi, Mina (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2015)
Introduction: We aimed to determine risk factors of postpartum depression in pregnant women. Material and methods: It was a prospective study on 143 pregnant women referred to health centers in Ramhormoz city during March 20 to September 21, 2013. The data collection tool was the Edinburgh questionnaire. The demographic data including age, education, occupation, spouse’s occupation, relative income of the family, satisfaction with child gender, frequency of prenatal care, history of nausea and vomiting in the first trimester of pregnancy, and abortion were collected. Data were entered into the SPSS software and analyzed using descriptive and analytical statistical tests such as sample t-test, one independent sample t-test, one-way ANOVA and 2 test. The significance level was considered 0.05. Results: A significant association was found between age of mother, parity, maternal education, satisfaction with gender of newborn, and method of delivery with postpartum depression (p < 0.05). The mean prevalence of postpartum depression was different in mothers with unwanted pregnancy, or newborn’s disease during birth (p < 0.05). Factors associated with postpartum depression were husband’s satisfaction with recent pregnancy, an unwanted pregnancy, satisfaction with gender of newborn, education levels, and stress levels during pregnancy. Conclusions: The prevalence of postpartum depression is high. Therefore, identification of risk factors associated with postpartum depression is essential to reduce the frequency of this disorder.